Disaster prevention management in the hotel industry: Hotel disaster prevention literacy. (December 2020) - Tsai, Chung-Hung; Linliu, Shu-Chuan; Chang, Richard C.Y.; Mak, Athena H.N.
Abstract: The purpose of this study is to develop an effective measure of hotel staff literacy in disaster prevention. This research was divided into two stages. First, a series of in-depth interviews and two rounds of modified Delphi method were used to derive the items and dimensions of hotel disaster prevention literacy. Four key dimensions were identified, namely, disaster prevention knowledge, disaster prevention attitude, disaster prevention skills, and disaster prevention services. Second, a one-group pretest-posttest experimental design was adopted to assess the effectiveness of disaster prevention training for hotel staff using the hotel disaster prevention literacy scale. The result revealed that staff who took part in the training displayed a significantly higher level of disaster prevention literacy in all four key dimensions compared with those who did not participate in the training. The results provide useful theoretical and practical insights into disaster prevention management in the hotel industry.